2011
DOI: 10.1007/s10384-011-0077-4
|View full text |Cite
|
Sign up to set email alerts
|

Malignant eyelid tumors in Hong Kong 1997–2009

Abstract: Increasing incidence of malignant eyelid tumors was noticed in Hong Kong from 1997 to 2009, with BCC dominating the incidence trend. Recurrence after complete surgical excision was uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…SGC is very rare in Western literature. However, SGC was the second most common malignant eyelid tumor in our series and accounted for 21.1%, which was similar to some studies in Asia [9, 1316]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SGC is very rare in Western literature. However, SGC was the second most common malignant eyelid tumor in our series and accounted for 21.1%, which was similar to some studies in Asia [9, 1316]. …”
Section: Discussionsupporting
confidence: 91%
“…BCC is the most common eyelid malignancy worldwide and accounts for 80–95% of all eyelid malignancy [5, 12]. However, in various Chinese studies, the percentage of BCC in all eyelid malignancy was not so much [4, 9, 13, 14]. In our study, BCC remained the most frequently malignant eyelid tumors (57.8%).…”
Section: Discussionmentioning
confidence: 44%
“…In general, BCC is the most common cancer of the eyelid accounting for about 65% of cases in Taiwan,2 90.8% in Minnesota,4 82.4% in Philadelphia13 and 75% in Hong Kong 14. These are in stark contrast to the proportion of histological diagnosis in India, China and in Japan.…”
Section: Discussionmentioning
confidence: 95%
“…I previously published an article titled "Malignant eyelid tumors in Hong Kong 1997-2009" in an overseas journal back in 2011 focusing on malignant eyelid tumours. 2 While both Ho and I found basal cell carcinoma (BCC) was the most common malignant eyelid tumour among Hong Kong Chinese, BCC constituted 75% of all malignant eyelid tumours as noted from my study in contrast to 43% as reported in Ho's paper.…”
mentioning
confidence: 60%